Preexposition Prophylaxis With Truvada (Tenofovir/Emtricitabine) as Potential Cause of Celiac Disease-Like Enteropathy - Pokryszka, Jagoda; Wichlas, Martina; Vogelsang, Harald; Trauner, Michael; Herac-Kornauth, Merima; Kazemi-Shirazi, Lili (Zeitschrift für Gastroenterologie, 2023)
We present here a case of a 39-year-old patient who presented with celiac-disease-like symptoms and MARSH 3a histology in duodenal biopsies under normal diet. Interestingly, HLA genotyping and celiac-specific serology were negative, primarily leading to exclusion of celiac disease. However, biopsies from a second endoscopy a couple of months later (still under normal diet) showed histologic progression of the disease to MARSH 3b and led to the re-evaluation of the out-of-hospital-obtained histological samples by a pathologist experienced in celiac disease. The second biopsy described previously as MARSH 3b turned out to be non-specific and was therefore re-classified as MARSH 0. After all known causes of duodenal villous atrophy were excluded by a thorough evaluation, a correlation between the first biopsy (MARSH 3a) and Truvada intake could be established. After Truvada discontinuation and under normal diet, normalisation of duodenal mucosa was observed, leading to the assumption that Truvada could lead to celiac-like enteropathy.
Keywords: celiac disease; Truvada; villous atrophy; MARSH